Features of the development of linguistic and communication competences of future foreign language teachers - Markova, Elena M.; Kuznetsova, Galina V.; Kozlova, Olga V.; Korbozerova, Nina M.; Domnich, Olga V. (Linguistics and Culture Review, 2021)
The relevance of the study is determined by the fact that the professional competence of a teacher constitutes a dynamic combination of knowledge, abilities and practical skills, ways of thinking, professional, ideological and civic qualities, moral and ethical values. The linguistic competence of the teacher depends entirely on the possibilities of professional growth and the dynamics of the development of professional and communicative competences. The novelty of the study is determined by the fact that in professional activity the teacher acts as an active subject of communication: transmits and accepts information from students, colleagues and parents, strives for the maximum realisation of the abilities of each student and ensuring their emotional comfort. The authors of this study have determined that one of the primary tasks of higher pedagogical education lies in the development of professional and pedagogical communicative competence of a teacher. The practical significance of the study is determined by the fact that professional and pedagogical communicative competence acts as a spiritual and moral factor and the scientific content of the educational process, where a major role is played by the teacher's knowledge, humanity, spiritual generosity, as well as the desire to understand and help the student.